Nitrate movement on surface and subsurface horizons of Udox and Udult soils with variable charges - Alcântara, Marco Aurélio Kondracki de; Camargo, Otávio Antonio de (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate nitrate movement on soil columns considering mainly, total amount recovered, fit among experimental and model‑predicted transposition curves, and model‑obtained retardation factors. Samples of A and B horizons of Udox and Udult soils were used. A leaching experiment was carried out considering the miscible displacement theory, using 100 mL of a 10-mmol L-1 KNO3 solution as pulse. The amounts of nitrate leached and recovered in the columns for Udox and Udult soils in horizons A and B varied from 0.405 to 1.432 mmol L-1. There was significant (p
Keywords: retardation factor; mathematical model; tropical soils